Alien Marine Species in the Mediterranean - the 100 ‘Worst Invasives’ and their Impact - STREFTARIS, N.; ZENETOS, A. (Mediterranean Marine Science, 2006)
A number of marine alien species have been described as invasive or locally invasive in the Mediterranean because of their proliferation, and/or their geographical spread and/or impact on native populations. Based on that information and on the documented impact they have on the biodiversity and socioeconomics of the basin, a preliminary list of the 100 ‘worst’ Invasive Alien Species (IAS) in the Mediterranean has been produced and presented in this work along with details on their impact. Emphasis is given to their impact on socioeconomics (fi sheries/aquaculture, health & sanitation, infrastructure & building), documented for 43 species. Such selection of the ‘worst’ IAS was diffi cult and controversial and is expected to attract much attention and scientifi c criticism since not only can the documentation of the impact of IAS be controversial, but also their inventory can be biased towards the effort and resources devoted to the study of the impact of certain species/taxonomic groups. Thus, while marine plants (phytobenthos and phytoplankton) are fairly well studied, less attention has been paid to the impact of vertebrates and even less to invertebrates. Nevertheless, the list highlights the need for continued research on the issue (monitoring aliens and their impact for an integrated ecosystem based management approach over the entire area). The preliminary list can provide the basis for selecting indicator species within the Mediterranean and thus be the common ground to build cooperation about IAS within countries in the region.